2022
DOI: 10.1093/ageing/afac051
|View full text |Cite
|
Sign up to set email alerts
|

Positive scores on the 4AT delirium assessment tool at hospital admission are linked to mortality, length of stay and home time: two-centre study of 82,770 emergency admissions

Abstract: Background Studies investigating outcomes of delirium using large-scale routine data are rare. We performed a two-centre study using the 4 ‘A’s Test (4AT) delirium detection tool to analyse relationships between delirium and 30-day mortality, length of stay and home time (days at home in the year following admission). Methods The 4AT was performed as part of usual care. Data from emergency admissions in patients ≥65 years in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…19 Long-term disability and death were more frequent than expected only for COVIDassociated cerebrovascular diseases and acute encephalopathy, compared with other known causes of the same disorders, in accordance with previous studies. [20][21][22] Diagnosis, treatment, data collection, and follow-up visits or calls were exclusively performed by neurologists who were involved in patient's management from hospital admission or were referred the patient by COVID physicians, intensivists, or infectious disease specialists at any time during the study period. This neurologist-centered approach of patient ascertainment had both advantages and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…19 Long-term disability and death were more frequent than expected only for COVIDassociated cerebrovascular diseases and acute encephalopathy, compared with other known causes of the same disorders, in accordance with previous studies. [20][21][22] Diagnosis, treatment, data collection, and follow-up visits or calls were exclusively performed by neurologists who were involved in patient's management from hospital admission or were referred the patient by COVID physicians, intensivists, or infectious disease specialists at any time during the study period. This neurologist-centered approach of patient ascertainment had both advantages and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the 4AT may be advantageous to use in EDs as it is shorter and simpler compared with other recommended tests and does not require any special training 50 . This is supported by one recent large observational study examining 4AT outcomes in the ED, which found that screening using this tool was feasible in a large ‘real‐world’ ED setting 51 …”
Section: Discussionmentioning
confidence: 85%
“…50 This is supported by one recent large observational study examining 4AT outcomes in the ED, which found that screening using this tool was feasible in a large 'real-world' ED setting. 51 The second area of discrepancy pertains to pharmacological management. Two CPGs recommend against using antipsychotic medications, such as haloperidol, to treat delirium under any circumstance.…”
Section: Managementmentioning
confidence: 99%
“…11 However, in clinical practice delirium can be difficult to diagnose and often goes unrecognized by clinicians, in up to 65% to 88% of cases. 2 Besides increased mortality, 12,13 delirium has also been associated with prolonged mechanical ventilations during ICU treatment, prolonged hospitalization and increased healthcare costs, 4,14,15 impaired physical functioning, [4][5][6]15 and cognitive disturbances and long-term cognitive decline. 7,14,16 Psychological symptoms such as anxiety, depression and posttraumatic stress have also been reported.…”
Section: Introductionmentioning
confidence: 99%